761PA national comparative effectiveness study to assess definitive chemoradiation regimens in proximal oesophageal squamous cell cancer. (1st October 2019) - de Vos-Geelen, J; Hoebers, F J P; Geurts, S M E; Hoeben, A; de Greef, B T A; Voncken, F E M; Bogers, J A; Braam, P M; Muijs, C T; de Jong, M A; Kasperts, N; Rozema, T; et al.
Abstract: Background: Proximal oesophageal cancer is commonly treated with definitive chemoradiation (CRT). The radiation dose and type of chemotherapy backbone in CRT are still under debate. The objective of this study is to compare the treatment benefit of four contemporary CRT regimens. Methods: In this retrospective observational cohort study, we included patients with locally advanced squamous cell cancer of the proximal oesophagus, from 11 centers in the Netherlands, treated with definitive CRT between 2004-2014. Each center had a preferential CRT regimen, based on cisplatin (Cis) or carboplatin/paclitaxel (CP) combined with low (≤50.4 Gy) or high (>50.4 Gy) dose radiotherapy (RT). Differences in overall survival (OS) between CRT regimens were assessed using a fully adjusted Cox proportional hazards and propensity score (PS) model. Safety profiles were compared using the Chi-square test. Results: Two-hundred patients were included. Fifty-four, 39, 95, and 12 patients were treated with Cis-low-dose RT, Cis-high-dose RT, CP-low-dose RT, and CP-high-dose RT, respectively. Median follow-up was 62.6 months (95% CI 47.9-77.2 months). Median OS (21.9 months; 95% CI 16.9-27.0 months) was comparable between treatment groups (logrank P = 0.88), confirmed in the fully adjusted and PS weighted model (P > 0.05). Grade 3-5 acute adverse events were less frequent in patients treated with CP-low-dose RT (P = 0.01). Conclusions: Our study results suggest that carboplatin and paclitaxel combined with RT at a dose of 50.4 Gy is the preferred CRT regimen in patients with locally advanced proximal oesophageal squamous cell cancer, showing comparable OS and a significantly more favourable safety profile when compared with cisplatin-based or higher RT dose regimens. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: J. de Vos-Geelen: Travel / Accommodation / Expenses: BTG; Research grant / Funding (institution), Travel / Accommodation / Expenses: Servier; Advisory / Consultancy: Shire. B.T.A. de Greef: Research grant / Funding (institution): Prinses Beatrix Spierfonds (W.OR12-01). H.W.M. van Laarhoven: Advisory / Consultancy, Research grant / Funding (institution): BMS; Advisory / Consultancy, Research grant / Funding (institution): Celgene; Advisory / Consultancy, Research grant / Funding (institution): Lilly; Advisory / Consultancy, Research grant / Funding (institution): Nordic; Research grant / Funding (institution): Bayer; Research grant / Funding (institution): Merck Serono; Research grant / Funding (institution): MSD; Research grant / Funding (institution): Philips; Research grant / Funding (institution): Roche. V.E.P.P. Lemmens: Research grant / Funding (institution): Roche. V.C.G. Tjan-Heijnen: Honoraria (self), Research grant / Funding (institution), Travel / Accommodation / Expenses: Roche; Honoraria (self), Research grant / Funding (institution), Travel / Accommodation / Expenses: Novartis; Honoraria (self), Research grant / Funding (institution), Travel / Accommodation / Expenses: Pfizer; Honoraria (self), Research grant / Funding (institution), Travel / Accommodation / Expenses: Lilly; Honoraria (self), Travel / Accommodation / Expenses: Accord Healthcare; Research grant / Funding (institution): AstraZeneca; Research grant / Funding (institution): Eisai. All other authors have declared no conflicts of interest.